"I felt more prepared and ready for clinic": Connections in student and clinical educator views about simulation-based learning - Adriana Penman; Anne E Hill; Sally Hewat; Nerina Scarinci
Clinical placements supported by a clinical educator in real clinical environments are beneficial for student learning. Student preparedness for placements has been examined across health professions. Simulation-based learning (SBL) is recognised as a valuable means of preparing students for practice. Whilst students' perceptions of SBL activities has been investigated, insights from clinical educators are less researched. This study aimed to explore speech pathology students' perceptions of clinical learning immediately following a SBL experience and perceptions of both the student and clinical educators following a subsequent clinical placement. Thirteen third year undergraduate speech pathology students and five clinical educators participated in this research. Students completed an SBL program prior to a six-week clinical placement. A student focus group discussion was held following the SBL experience and semi-structured interviews were conducted with individual students and clinical educators at the completion of placement. Thematic analysis of the data was conducted and themes were summarised using a thematic network tool. Overall interpretation of data from the students' and clinical educators' perspectives revealed an overarching global theme suggesting that simulation offers unique learning benefits to prepare students for typical clinical placement. As students and clinical educators demonstrated shared perceptions that SBL offers unique learning benefits for speech pathology students, this finding further supports the inclusion of SBL within university program curricula.